Productive Waqf in Islamic Banking as Transformative Economic Behavior in Realizing Sustainable Development Goals - Faza, Iqbal; Atabik, Ahmad; Karim, Abdul (ZISWAF, 2026)
This study examines the role of productive waqf within Islamic banking as a form of transformative economic behavior and explores its potential contribution to the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), and SDG 10 (Reduced Inequalities). A systematic conceptual analysis was employed using peer-reviewed journal articles, books, institutional reports, regulatory documents, and selected grey literature published between 2003 and June 2026. The analysis applied thematic synthesis to investigate four interconnected dimensions: productive waqf as an institution, Islamic banking as a facilitating mechanism, transformative economic behavior as a conceptual lens, and the SDGs as an outcome framework. The findings suggest that integrating productive waqf with Islamic banking can generate a multiplier effect through waqf asset mobilization, financial inclusion, and socio-economic empowerment. The study advances three key propositions. First, Islamic banks may serve as strategic nazir partners without compromising governance boundaries when supported by appropriate regulatory frameworks. Second, productive waqf represents a form of transformative economic behavior when it promotes structural change, is grounded in Islamic values, and strengthens community agency. Third, the contribution of productive waqf to the SDGs becomes more measurable when operationalized through a mechanism-based pathway linking inputs, contractual vehicles, outputs, outcomes, and SDG indicators. This study contributes to the literature by proposing a mechanism-based SDG linkage framework, offering an operational definition of transformative economic behavior rooted in maqāṣid al-sharīʿah, and clarifying the governance boundaries of Islamic bank involvement in productive waqf management.